2020
DOI: 10.1074/jbc.ra120.015237
|View full text |Cite
|
Sign up to set email alerts
|

An automated, high-throughput methodology optimized for quantitative cell-free mitochondrial and nuclear DNA isolation from plasma

Abstract: Progress in the study of circulating, cell-free nuclear DNA (ccf-nDNA) in cancer detection has led to the development of non-invasive clinical diagnostic tests and has accelerated the evaluation of ccf-nDNA abundance as a disease biomarker. Likewise, circulating, cell-free mitochondrial DNA (ccf-mtDNA) is under similar investigation. However, optimal ccf-mtDNA isolation parameters have not been established, and inconsistent protocols for ccf-nDNA collection, storage, and analysis have hindered its clinical uti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…To ensure the absence of cell and cell debris, each saliva sample was further centrifuged at 2,000 × g for 10 minutes at 4°C prior to processing. To avoid bias in mtDNA content that may occur during DNA isolation using column-based methods (43), DNA was extracted using an isolation-free lysis method, adapted from (44). 20 ul of saliva was added to 180ul of lysis buffer (500mM Tris HCL, 1% Tween 20, dH 2 0, and 20ug/ml proteinase K), for a dilution of 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the absence of cell and cell debris, each saliva sample was further centrifuged at 2,000 × g for 10 minutes at 4°C prior to processing. To avoid bias in mtDNA content that may occur during DNA isolation using column-based methods (43), DNA was extracted using an isolation-free lysis method, adapted from (44). 20 ul of saliva was added to 180ul of lysis buffer (500mM Tris HCL, 1% Tween 20, dH 2 0, and 20ug/ml proteinase K), for a dilution of 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid bias in the extraction of either mtDNA or nDNA using standard DNA isolation kits ( Guo et al, 2009 ; Fazzini et al, 2018 ), lysis based methods which can be combined with DNA retrieval methods ( Kolesar et al, 2012 ) appear to be optimal. Optimized high-throughput methods have recently been reported that increase the efficiency of mtDNA recovery by 95-fold and nDNA recovery by 20-fold ( Ware et al, 2020 ).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Culture media was collected and stored at -80°C until analyzed as a single batch. Total cell-free DNA (cf-DNA) was isolated from 75 µL f cell culture media using an automated, high throughput methodology previously published 105 , using the MagMAX Cell-Free DNA Isolation Kit based on MagMAX™ magnetic-bead technology (Thermo Fisher Scientific). Duplex qPCR reactions with Taqman chemistry were used to simultaneously quantify mitochondrial (cf-mtDNA, ND1) and nuclear (cf-nDNA, B2M) amplicons, using the same primers and probes described in the mtDNA copy number section.…”
Section: Methodsmentioning
confidence: 99%